Business process improvement toolbox - Andersen, Bjørn (ASQ Quality Press, 2007)
"The first half of the book presents an overall business process improvement model, with the ensuing chapters dealing with topics of understanding and modeling your current business processes, using performance measurement in improvement work, creating a business process improvement road map, and organizing for improvement work. The second half of the book presents the overall toolbox, followed by one chapter for each phase of the overall improvement model. For each of these phases, a selection of suitable tools is presented with background, steps for how to use them, and an example of their use. The final two chapters contain two more extensive case studies illustrating the use of the full methodology.